Konsep Evaluasi Diri dalam Persfektif Al-Qur’an - Savira, Izza Aulia (TSAQOFAH, 2023)
The concept of self-evaluation is an achievement of oneself. Which in every day we must have made mistakes. For this reason, it is necessary for each individual to evaluate every immoral act or act prohibited by Allah SWT in order to make us human beings who are of a higher quality before Allah SWT. The purpose of this study is to find out the concept of self-evaluation in the Koran. This research is included in library research (Library Research), namely research conducted using literature (library) in the form of commentary books such as the interpretations of At-Tabari, Ibn Katsir, Al-Azhar, Sya'rawi, and Al-Misbah, as well as books, theses or journals that study related to the concept of self-evaluation which is descriptive analysis, namely analyzing from several interpretation books taken as a reference. The approach used in this study is the Maudhu'i (thematic) interpretation method approach, namely looking at themes related to the concept of self-evaluation in the Koran. The method used is the content analysis method, namely analyzing the interpretation of the mufassir figures on verses related to self-evaluation. Based on the results of the research that the writer has done, it can be concluded that the writer does not find many verses that directly discuss self-evaluation, but here the writer takes several verses and the interpretations of the commentators related to self-evaluation. The author takes the interpretations of Imam Ath-Tabari, Ibnu Katsir, Buya Hamka, Imam Asy-Sya'rawi, and M. Quraish Shihab. Which they explain the need to evaluate themselves by leaving all the immorality that is forbidden by Allah and doing good deeds ordered by Allah, where each of these deeds will be accounted for in the afterlife.